The radical left and its political communication. An examination of the campaign activities of radical left candidates in sixteen Europe countries - Katsourides, Yiannos; Ioannidis, Nikandros (My University, 2024)
In this paper we focus on the political communication activities of the candidates of the radical left parties (RLPs), emphasizing their campaign activities during electioneering. We aim to address three key questions. First, we seek to understand what type of political communication activities RLP candidates use. Second, we undertake a comparative analysis, contrasting these activities with those employed by candidates and MPs from other party families in order to identify any notable distinctions. Third, we explore the thematic emphasis of their campaign activities and whether it aligns with the commonly held perception of RLPs as less individualistic, particularly in light of the prevailing trend towards increased personalization in politics. Our data come from the Comparative Candidates Survey (CCS) and cover 16 European countries over the years spanning from 2005 to 2017. In sum, the findings present a nuanced perspective and do not conclusively demonstrate a distinctly unique type of candidate of the radical left.